2019
DOI: 10.1111/ctr.13583
|View full text |Cite
|
Sign up to set email alerts
|

Impact of asymptomatic bacteriuria incidence and management post–kidney transplantation

Abstract: Objective Urinary tract infections (UTIs) are the most commonly occurring infectious complication following kidney transplantation. Questions remain regarding whether asymptomatic bacteriuria (ASB) should be treated. The aim was to evaluate the incidence and management of ASB in kidney transplant recipients at a large academic medical center. Methods All subjects receiving an isolated kidney transplant between September 2012 and October 2016, and with at least one ASB episode were included. Demographics, sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Moreover, the treatment of ASB has been associated with antibiotic harmful effects such as the development of multidrug-resistant (MDR) bacteria, a higher incidence of Clostridium difficile diarrhea, and increased healthcare costs [49]. Concern about ASB in the first 1-3 months after transplantation has been raised due to higher immunosuppression and surgical manipulation immediately post-transplant, however, there is not enough evidence to support this [50]. Thus, recent guidelines do not recommend routine screening and treatment of ASB in KT patients [2,3,47], however, screening can be considered in the first 1-3 months post-transplant, and treatment only if there have been two consecutive positive urine cultures for the same bacteria.…”
Section: Diagnosismentioning
confidence: 99%
“…Moreover, the treatment of ASB has been associated with antibiotic harmful effects such as the development of multidrug-resistant (MDR) bacteria, a higher incidence of Clostridium difficile diarrhea, and increased healthcare costs [49]. Concern about ASB in the first 1-3 months after transplantation has been raised due to higher immunosuppression and surgical manipulation immediately post-transplant, however, there is not enough evidence to support this [50]. Thus, recent guidelines do not recommend routine screening and treatment of ASB in KT patients [2,3,47], however, screening can be considered in the first 1-3 months post-transplant, and treatment only if there have been two consecutive positive urine cultures for the same bacteria.…”
Section: Diagnosismentioning
confidence: 99%
“…Three studies evaluated the incidence of ASB during the first month after KT, finding a pooled incidence of 22% for the first month after KT (Figure S3) with almost no heterogeneity . On the other hand, 10 studies reported data regarding the incidence of ASB during the first year after KT, finding an overall value of 32% (Figure S4) with significantly high heterogeneity (99%) …”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were included in this meta‐analysis; summaries of each are found in the web‐only Table S1 . When comparing ASB treatment (n = 500) to no treatment (n = 853), the relative risk (RR) for symptomatic UTI occurrence among treated patients was not significantly lower than the risk of not treated ones (OR 1.08; 95% CI 0.63‐1.84), with a moderate heterogeneity ( I 2 35%)(Figure ). On the other hand, three studies evaluated the impact in the graft function, described as the difference in the creatinine serum levels at the beginning and the end of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another observational study by Bohn et al [ 36 ] was conducted to assess the incidence of asymptomatic bacteriuria among patients that underwent kidney transplantation and whether the administration of antibiotics was efficacious in eliminating the infection and enhancing the prognosis or not. They reported that among 527 patients, the incidence was 12.1%, of which, three-fourths were treated were systemic antibiotics.…”
Section: Reviewmentioning
confidence: 99%